Clot composition in retrieved thrombi after mechanical thrombectomy in strokes due to carotid web. (29th January 2021) - Koneru, Sitara; Nogueira, Raul G; Osehobo, Ehizele; Oprea-Ilies, Gabriela; Al-Bayati, Alhamza R; Brinjikji, Waleed; Dai, Daying; Haussen, Diogo C
Abstract : Background: The association of carotid webs (CaW) and ischemic stroke is being increasingly recognized. Data on the histologic clot architecture in strokes caused by CaW has not been previously described. Understanding thrombi histopathology may provide insight into the pathophysiology of CaW-related strokes. Methods: This case series presents three patients with acute ischemic stroke thought to be caused by ipsilateral CaW. Thromboemboli were retrieved from the middle cerebral artery (MCA) by mechanical thrombectomy and histologic analysis was performed. Results: Three patients aged between 41 and 55 years with few to no vascular risk factors presented with symptoms concerning for an acute MCA territory infarction (National Institutes of Health Stroke Scale (NIHSS) range 10–17). Non-contrast computed tomography (CT) Alberta Stroke Program Early CT Score (ASPECTS) range was 7–8 and all patients had hyperdense vessel sign. Initial CT angiogram was concerning for CaW with no superimposed thrombus, later confirmed with conventional angiography. All patients underwent thrombectomy with full reperfusion. Comprehensive stroke workup failed to reveal other etiologies besides ipsilateral CaW. The histopathologic appearance was of typical fresh mixed thrombi. Qualitative thrombus composition analysis of clot from Case #1 yielded 42.5% fibrin, 50.0% red blood cells (RBC), and 7.5% white blood cells (WBC); Case #2 yielded 46.9% fibrin, 43.4% RBC, and 9.7% WBC; and Case #3 yielded 61.5% fibrin, 31.8% RBC, and 6.7% WBC. Conclusions: The clot composition of large vessel occlusion strokes from CaW is comparable to the histopathology of previously reported clots from other stroke etiologies. Advanced staining techniques may aid in further characterizing the thrombi of this poorly understood condition.